Island infernos : the US Army's Pacific War odyssey, 1944 - McManus, John C., 1965- (Dutton Caliber, Penguin Random House LLC, 2021)
"From the author of Fire and Fortitude, the continuation of the US Army's epic crusade in the Pacific War, from the battle of Saipan to the occupation of Japan"--